Tinjauan Yuridis Terhadap Perilaku Aparatur Negara Republik Indonesia Dalam Tatanan Administrasi Negara - Christine S.T. Kansil; Nethania Aurelia Madelin (LPPM Universitas Ekasakti Padang, 2024)
State officials are people who are used as instruments in government. Even though it has been regulated in the law regarding Government Administration, in practice there are still many problems that hinder it. The behavior of state officials who tend to abuse their authority is a problem that hinders the proper running of government administration. This paper aims to reduce the problems caused by several state officials who tend to abuse their authority. In Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, it is written that an official who commits an act of corruption because he abuses the authority of his position, resulting in harm to the state, then this behavior constitutes an abuse of the authority of his position. The method used in this writing is normative and quantitative. Apart from that, this research uses legislation and case decisions as a primary legal material approach and literature studies as a secondary legal material approach. Article 17 paragraphs (1) and (2) of Law No. 3 of 2014 regulates the prohibition of abuse of authority, where government officials are prohibited from abusing their authority.